Safety and satisfaction of patients with nurse's care in the perioperative - Sillero-Sillero, Amalia; Zabalegui, Adelaida (Revista latino-americana de enfermagem, 2019)
to investigate the safety and satisfaction of patients and their relationship with nurse's care in the perioperative period. cross-sectional, multi-level, correlational study with 105 nurses in the surgical area and 150 patients operated in a Spanish tertiary hospital. For the nurses the sociodemographic variables, the perception of the work environment, the professional burnout and the satisfaction in the work were collected. For patients, the safety of adverse events and level of satisfaction, through the application of questionnaires. Univariate and multivariate analysis were used. job satisfaction, professional commitment, and participation in hospital issues were negative predictors for adverse events related to the patient, while postoperative nurse care was a positive predictor. there is an increase in adverse events when nurses are dissatisfied at work, less professional commitment and low availability to participate in the subjects of their unit. On the other hand, adverse events decrease when nurses perform the care in the postoperative period. Satisfaction was good and there was no association with the characteristics of nurses' attention. It is recommended to improve these predictors to increase the safety of surgical patients.